PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI POKOK HUKUM-HUKUM DASAR KIMIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA (Kelas X MIPA SMAN 2 Teluk Kuantan) - Emelda Emelda; Nofri Yuhelman; Jumriana Rahayu Ningsih (Universitas Islam Kuantan Singingi, 2020)
This research aims to improve student learning outcomes through learning models in the basic laws of chemistry in the class MIPA X SMAN 2 Teluk Kuantan. This type of reaserch is classroom action research conducted in three cycles. The stages of research in each cycle include the planning of observation and reflection actions which are adopted from Kemmis dan Mc.Taggart. The research instrument used was an observation sheet and a test. Subjects in this study were students of class X MIPA SMAN 2 Teluk Kuantan who numbered 29 students. As for the minimum completeness criteria that are set >78. For classical learning mastery expressed successful if the percentage of students completing learning reaches 85% from the number of students. From the research it was found that the average completeness of individuals in cycle 1 was 57,2%, with the percentage of classical completeness student learning outcomes 3,44%%, and in cycle 2 the average individual completeness 72,4% the classical completeness percentage is 48,27% and in cycle 2 the average individual completeness 87,2% the classical completeness percentage is 86,2%. From these result it can be concluded that learning by using the problem based learning model of learning on the basic laws of chemistry can improve student learning outcomes. Kata Kunci: model Problem Based Learning (PBL); hasil belajar